The complete mitochondrial genome sequence of Drepanidotaenia lanceolata (Cyclophyllidea: Hymenolepididae). (4th May 2017) - Gao, Jun-Feng; Hou, Mei-Ru; Cui, Yu-Chao; Wang, Li-Kun; Wang, Chun-Ren
Abstract: The complete mitochondrial genome of Drepanidotaenia lanceolata was sequenced. The complete mtDNA sequence is 13 573 bp long and contains 12 protein-coding genes ( cox 1–3, nad 1–6, nad 4L, atp 6, and cyt b), two ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and 2 non-coding regions (NCR). Phylogenetic analysis using three methods (Bayesian inference, maximum parsimony, and maximum likelihood) demonstrates with high statistical support that D. lanceolata is closely related to the genus Hymenolepis . This study reports the first complete mt genome sequence of a representative species of the genus Drepanidotaenia and should provide novel genetic data for further studies of the taxonomy, systematics, and population genetics of these and other related cestodes of socio-economic significance.